Striving for normality: Agency, citizen participation and intergroup belonging on the urban periphery of Helsinki - Tuominen, Pekka (Frontiers in Sustainable Cities, 2022)
This article examines how the inhabitants of a culturally diverse suburban estate in Finland strive for meaningful encounters in their lives. The focus is on Kontula, a residential working-class district on the eastern periphery of Helsinki, which has become a powerful symbol of the ills of contemporary urbanity—poverty and social problems, as well as rootlessness and the failed integration of the immigrant populations—in the vernacular geography and media representations of the city. I studied how everyday mobility in an increasingly segregated city is related to a range of qualities of sociocultural encounters, both within the immediate neighbourhood and across other urban areas. I argue that for many marginalised inhabitants, agency predominantly emphasises striving for normality, not a challenge to the system. This is why it is so rarely recognised. Themes such as common decency, meaningful activity and equal encounter are much more typical aims of everyday practises than those focussing on changing the conditions. The contexts explored range from the familiar and neighbourly surroundings characterised by high degree of cultural intimacy and effortlessness to spaces with unfamiliar expectations and very different cultural codes. How do people living on the stigmatised periphery establish sense of belonging in a segregated city? How is it possible retain a sense of decency and dignity in unpredictable circumstances? During my long-term ethnographic fieldwork in the area, I concentrated on the qualities of encounters and senses of agency. These are interweaved with the inhabitants' everyday life, realised in their movement across the city and vary considerably in different contexts, reproducing the quotidian urbanity of Helsinki.